Exergy analysis of marine steam turbine labyrinth (gland) seals - Lorencin, Ivan; Anđelić, Nikola, inženjer strojarstva; Mrzljak, Vedran; Car, Zlatan, inženjer strojarstva (2019)
The paper presents an exergy analysis of marine steam turbine labyrinth (gland) seals - an inevitable component of any marine steam turbine cylinder, in three different operating regimes. Throughout labyrinth seals, steam specific enthalpy can be considered as a constant because the results obtained by this assumption do not deviate significantly from the results of complex numerical models. Changes in labyrinth seals exergy efficiency and specific exergy destruction are reverse proportional. The analyzed labyrinth seals have high exergy efficiencies in each observed operating regime at the ambient temperature of 298 K (above 92%), what indicates seals proper operation. An increase in the ambient temperature resulted with a decrease in labyrinth seals exergy efficiency, but even at the highest observed ambient temperature of 318 K, seals exergy efficiency did not fall below 90.5% in each observed operating regime.
Bibliografija: 30 jed.
Summary.
Keywords: Parne turbine -- Morske parne turbine -- Eksergija -- Eksergijski gubitak